1995
DOI: 10.1128/jvi.69.5.2912-2917.1995
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcription of baculovirus late and very late promoters: fractionation of nuclear extracts by phosphocellulose chromatography

Abstract: An in vitro transcription system based on a cytidine-free cassette was developed for the late 39k gene and the very late polyhedrin gene of Autographa californica nuclear polyhedrosis virus (AcNPV). Optimization of transcription conditions revealed that a preincubation step was not required for transcription of late and very late promoters, although preincubation was essential for efficient transcription from an early promoter. The 39k and polyhedrin constructs were actively transcribed by nuclear extracts pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…AcNPV RNA polymerase was purified from S. frugiperda cells infected with a recombinant baculovirus that overexpresses all four RNA polymerase subunits as described previ-ously (11). The purified RNA polymerase was filtered through a Superose 6 size exclusion column in 2 M KCl, and individual fractions were tested for RNA polymerase activity in our standard in vitro transcription assay (31). This assay uses two nucleoside-free templates that are separately linked to the late 39k gene and the very late polyhedrin gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AcNPV RNA polymerase was purified from S. frugiperda cells infected with a recombinant baculovirus that overexpresses all four RNA polymerase subunits as described previ-ously (11). The purified RNA polymerase was filtered through a Superose 6 size exclusion column in 2 M KCl, and individual fractions were tested for RNA polymerase activity in our standard in vitro transcription assay (31). This assay uses two nucleoside-free templates that are separately linked to the late 39k gene and the very late polyhedrin gene.…”
Section: Resultsmentioning
confidence: 99%
“…Much of our understanding of the mechanisms that control the temporal expression of baculovirus genes is derived from in vitro transcription systems. We and others have shown that in vitro extracts faithfully reproduce the temporal progression of viral gene expression (12,17,31). Recently, we used an in vitro transcription assay to purify the RNA polymerase that transcribed late and very late baculovirus genes.…”
mentioning
confidence: 99%
“…RNA polymerase was purified from Spodoptera frugiperda cells infected with vBAC-RNA pol as previously described (13). In vitro transcription assays were performed as described by Xu et al (41).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were lysed in 5 ml of lysis buffer, and the nuclei were pelleted as described previously (2). Further treatment of the nuclei was carried out as described by Xu et al (58). The pelleted nuclei were resuspended and lysed, and globular nuclear proteins were precipitated by the dropwise addition of ammonium sulfate (0.33 g per ml of supernatant).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro transcription assay. In vitro transcription was carried out essentially as described earlier (58), with minor modifications. The transcription reaction was carried out in a 50-l reaction volume with 1.5 g of the plasmid construct pPolh/CFS containing a C-free cassette (58) as the template and 50 g of protein prepared as described by Xu et al from AcNPV-infected Sf21 cells 36 h p.i.…”
Section: Methodsmentioning
confidence: 99%